KAJIAN SUMUR RESAPAN ANTISIPASI GENANGAN AIR PADA PERUMAHAN PERMATA KENALI UNTUK PENCEGAHAN BANJIR - Azwarman Azwarman (Universitas Batanghari Jambi, 2015)
In Indonesia regularly occur climate change from the dry season to the rainy season every year. Increased development of community life means triggering change in land use is causing a shortage of open land as a catchment area. This leads to runoff and only a little rainwater that falls tanah.Hujan absorbed by the roof surface and ground houses could cause flooding. Especially in residential areas that have little existing land plants.To anticipate the occurrence of flooding, it is necessary to make infiltration wells on each housing residents. Infiltration wells serves to accommodate and absorb rainwater into the soil slowly.Based on data analysis and calculation according to SK SNI 03-2453-2002, can be determined recharge wells were circular with a diameter of one meter and a depth of 3 meters. Construction recharge wells that correspond according to the instructions Technical Implementation Procedures Drainage environmentally sound Settlement Region (2002) is a brick wall without plaster or brick red and given the holes in the walls.keyword : rain water , the flow of the surface , absorption wells